Razvoj pripomočkov za merjenje otroškega govora v slovenskem prostoru - Kranjc, Simona (Slavistična revija, 2007)
The authors presents an original Slovene instrument of assessment of children's language from ages four to six that was developed based on the analysis of foreign tests and authors' own research. While the criteria for assessment of child's story have been presented in detail in Slovenia and elsewhere, the present article presents the Scales of general language development (LSGR - LJ), which are currently in the process of standardization and which will have not only research, but also broader applications. LSGR -LJ is comprised of three scales, i.e., Scale of language comprehension, Scale of language expression, and Scale of metalinguistic awarmess. The latter scale is given to five- and six-year-olds younger children who have solved tasks for five year-olds on the scales of verbal expression, while the former scales are given to children starting at two years of age. The instrument contains 221 tasks, however, each child only solves the tasks appropriate to his/her chronological age and language competence. - Previous studies have shown that LSGR - LJ is a highly reliable instrument. In addition, it satisfies the criteria of content, construct, and convergence validities.
Keywords: assessment of children's language; children's language; child's story-telling; govorni razvoj; language development; lestvice splošnega govornega razvoja; ocenjevanje otrokovega govora; otrokovo pripovedovanje zgodbe; otroški govor; scales of general language development; Slovene language; slovenščina